Physio-morphological and molecular analysis for salt tolerance in chickpea (Cicer arietinum) - KUMAR, NEERAJ; BHARADWAJ, C; SONI, ANJALI; SACHDEVA, SUPRIYA; YADAV, M C; PAL, MADAN; SOREN, K R; MEENA, M C; ROORKIWAL, MANISH; VARSHNEY, RAJEEV KUMAR; RANA, MANEET (The Indian Journal of Agricultural Sciences, 2025)
After drought salinity is the major abiotic stress that severely affects agricultural productivity globally. Chickpea (Cicer arietinum L.) is the important grain legume which suffers approximately 8-10% of total global yield loss due to salinity. Screening for salt stress is difficult and traits that correlate salinity tolerance are least understood. The present study was carried out at ICAR-IARI, New Delhi 2017-18, deals with the important morphological and physiological traits like RWC (Relative water content), EL (Electrolyte Leakage), Na/K (sodium and potassium ratio) to characterize the salt tolerant genotypes under hydroponic condition which is a quick and easy method to screen large number of chickpea genotypes at initial stage under salt stress condition. Genotypes showing high RWC, low EL and Na/K ratio were tolerant like ICCV 10, JG 11, JG 62 and CSG-8962 whereas genotypes like ICC4958 and Pusa362 fall under moderately tolerant genotypes and DCP 93-3, Pusa 256, Phule G5 and SBD 377 were classified as susceptible genotypes. This study also attempts to understand the candidate genes responsible for salt-stress related pathways in chickpea genotypes based on sequence similarity approach exploiting known salt-stress responsive genes from model crops or other crop species.